Regional Income Convergence Analysis in East Java: Does Investment Matter? - Mohammad Ichsan Verianto; Rosa Diwanegara (East Java Economic Journal, 2022)
The convergence hypothesis in the Neo-Classical growth approach says that a region or country with a low per capita income will experience faster catch-up growth than a richer country. However, the theory of endogenous growth, as well as New Economic Geography (NEG), states that divergence occurs. The contradictions among those theories become the basis of this research. This study uses a case study of East Java because it has a relatively large share of PDRB to GDP, but still has a relatively high inequality. This study aims to examine the effect of government investment on the convergence of economic growth in East Java. This study uses per capita Gross Regional Domestic Product (PDRB) and Gross Fixed Capital Formation (PMTB) accessed from the annual report of the Central Bureau of Statistics in each city in East Java during the period 2010 to 2021. The results of the study show that -convergence and -convergence both have a divergence process. This study provides policy recommendations in the form of concentrating investment in new central areas as the formation of centers of economic growth, such as Special Economic Zones (SEZ) in the southern region of East Java.